2015
DOI: 10.1007/s12540-015-4394-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of laser beam welding transverse-varestraint test for assessment of solidification cracking susceptibility in laser welds

Abstract: In order to quantitatively evaluate the solidification cracking susceptibility in laser welds of type 310S stainless steel, a transverse-Varestraint testing system using a laser beam welding apparatus was newly constructed. The timing-synchronization between the laser oscillator, welding robot and hydraulic pressure devices was established by employing high-speed camera observations together with electrical signal control among the three components. Moreover, the yoke-drop time measured by the camera was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 28 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…The difference of the BTR is around 10°C in the Chun et al data due to the small change of the segregated concentration at different welding speeds from 0.6 to 2.4 m/min. 5) While, in this study, the deviation of the BTR is also about 10°C which is close to that of Chun et al, 5) as shown in Fig. 10, therefore, it is reasonable and believable that the average BTR is nearly similar in this case.…”
Section: The Temperature Range Of the Solidificationsupporting
confidence: 89%
See 1 more Smart Citation
“…The difference of the BTR is around 10°C in the Chun et al data due to the small change of the segregated concentration at different welding speeds from 0.6 to 2.4 m/min. 5) While, in this study, the deviation of the BTR is also about 10°C which is close to that of Chun et al, 5) as shown in Fig. 10, therefore, it is reasonable and believable that the average BTR is nearly similar in this case.…”
Section: The Temperature Range Of the Solidificationsupporting
confidence: 89%
“…Chun et al have reported that the BTR tended to decrease with increasing welding speeds from 0.6 to 2.4 m/min during the laser Trans-Varestraint test for type 310S stainless steel. 5) However, the BTR was measured using a thermocouple with a relative low response rate, providing a result that was less accurate than the method used herein. In addition, the authors (Wang et al, 2015) have previously developed a laser Trans-Varestraint test at different welding speeds from 0.2 to 2.0 m/min, and the BTR could be measured by applying an optical fiber radiation thermometer with a relative high response rate at welding speed of 0.2 m/min.…”
Section: Introductionmentioning
confidence: 92%
“…The Varestraint test, proposed by Savage in 1965 [1], has been used for evaluating the susceptibility of weld hot cracking. Since then, many researchers have reported the evaluation result of weld hot cracking susceptibility using the Varestraint test [2][3][4][5][6][7][8][9]. Several approaches in the Varestraint test have been reported for evaluating the type of crack.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the GTAW is used as a heat source in the above test methods to evaluate the solidification cracking susceptibility. While there are few test methods to evaluate the susceptibility during laser welding, Shinozaki [ 17 , 18 , 19 , 20 , 21 , 22 ] et al developed a U type hot cracking test based on laser welding and laser Trans-Varestraint test [ 17 , 18 , 19 , 20 , 21 , 22 ] to evaluate solidification cracking susceptibility of stainless steel quantitatively. Nevertheless, these methods are difficult to adopt for widespread use, since it is hard to measure temperature accurately during laser welding at high welding speed and also it needs expensive equipment, such as the Varestraint test machine, high-speed camera, and high precision temperature measurement device and so on.…”
Section: Introductionmentioning
confidence: 99%